Cymru Yfory: Incrementalism or Transformation for the Regional Economy? - Calvin Jones (Revue Française de Civilisation Britannique)
Wales has economically underperformed its European neighbours for decades. As societies and economies transform in response to key climate, nature and technological pressures, this paper asks whether recent policy innovations in Wales, the result of political devolution from London, signal a new radicalism. Will this comprise a different approach to regional development, one that values the local over the global, and wellbeing over economic growth, resulting in a more resilient, sustainable and responsible region?